Effectiveness of Placing Attack Detection Detectors - et. al., Vyacheslav L. Tokarev, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The effectiveness of intrusion detection systems based on immune detectors requires rational placement of immune detectors on network nodes. For this, it is necessary to determine the risk of violating the information security of the computer network. Evaluating the network nodes’ security risk is complicated by the number of vulnerabilities. To solve this problem, it is proposed to use a statistical formal model based on Markov chains in combination with vulnerability analysis metrics. To analyze vulnerabilities, we use scoring scores as metrics of basic, temporal, and contextual types. The main component of the proposed model is the graph of possible trajectories. An example network was used to test the proposed model. A formal model of information security risk assessment allows identifying critical nodes along the path of access to the target node that makes it possible to install immune detectors on these nodes in order to improve the protection system.